2017
DOI: 10.1186/s13027-017-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after sofosbuvir-containing regimens for hepatitis C virus in patients with decompensated cirrhosis: a real-world study

Abstract: BackgroundDirect-acting antivirals have been used for decompensated cirrhotic patients with hepatitis C virus (HCV) infection. However, the benefits in Chinese patients with decompensated cirrhosis are unclear.MethodsThirty patients with HCV infection and decompensated cirrhosis were administered sofosbuvir-containing regimens at our hospital between April and December 2015. The efficacy and safety of the treatments was determined by sustained virological response at week 12 (SVR 12), change of liver function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…In this study, we demonstrated for the first time that patients with previous placement of TIPS can achieve optimal rates of SVR24 (92.5%) and a significant decrease in MELD and MELD-Na score from T0 to W24. In particular, both SVR rate and the improvement of liver function in patients with prior placement of TIPS treated with DAA are coherent with previous studies in patients with advanced cirrhosis without TIPS [6,20]. It should be noted that in patients with TIPS the decline of MELD was somehow slower than in patients without TIPS.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we demonstrated for the first time that patients with previous placement of TIPS can achieve optimal rates of SVR24 (92.5%) and a significant decrease in MELD and MELD-Na score from T0 to W24. In particular, both SVR rate and the improvement of liver function in patients with prior placement of TIPS treated with DAA are coherent with previous studies in patients with advanced cirrhosis without TIPS [6,20]. It should be noted that in patients with TIPS the decline of MELD was somehow slower than in patients without TIPS.…”
Section: Discussionsupporting
confidence: 87%
“…This is supported by a recent study from Egypt involving 2400 patients with HCV-related cirrhosis, where sofosbuvir and ribavirin therapy lead to SVR in only 71.2%, with more than 5% of patients discontinuing therapy due to adverse effects 21. In a Chinese study, patients with HCV-related decompensated cirrhosis achieved 90% SVR;23 however, this likely relates to the small number of patients (n=30).…”
Section: Discussionmentioning
confidence: 77%
“…25 Recent medical literature suggests that ribavirin-unrelated anaemia is uncommon in HCVinfected patients who undergo treatment with DAAs. 26,27 The management of anaemia in our study required blood transfusions in seven patients. Therefore, we suggest a careful monitoring of Hb levels during antiviral therapy with DAAs.…”
Section: Discussionmentioning
confidence: 99%